Begin with The End in Mind: Storying The Post-Pandemic PhD - Tara Brabazon (International Journal of Social Sciences & Educational Studies, 2022)
This study investigated the undergraduates’ satisfaction with blended learning in a private Higher education institute in Lebanon amid what is undoubtedly described as a ghastly era that resulted in a financial meltdown with a lack of liquidity. The survey, compiling the major features of blended learning integral to students’ satisfaction, was administered to 226 undergraduates at USAL (University of Sciences and Arts in Lebanon) from the majors of education, business, media, and computer sciences. The survey addressed three different dimensions of blended learning that are recognized as basics in the related literature, and they included the technology, the interactivity &engagement, and the instructor/instruction. Data were analyzed using SPSS 26.0 for windows. Results indicated a considerable satisfaction with blended learning with an alerting concern about the instructors’ readiness and to how qualified they were to handle blended learning efficiently. Recommendations are shared in terms of policy and practice of blended learning in Higher education context.